IMPROVEMENT SUGGESTION IN A COMPANY’S FORGING PROCESS USING THE QUALITY TOOL ISHIKAWA DIAGRAM - Santos, Edimar de Souza; Okada, Roberto Hirochi (Revista Interface Tecnológica, 2021)
This article presents a study on the use of the Ishikawa Diagram quality tool. The purpose of this study was to show how important quality tools are for the pursuit of continuous improvement of their products through process improvement. The Ishikawa Diagram tool allows organizing information to identify the possible causes and effects of the problem, showing the causes that may contribute to the problem occurring. For the application of the tool, a study was made in academic articles about the forging process and how it is possible to apply the Ishikawa diagram to find the cause of non-conformity in a part, spherical grinding bodies with nominal diameter of 90mm was built by company X (company name not disclosed). With the completion of the results of the application of the tool, suggestions can be made to improve the production process and thus achieve better satisfaction for the company and customers.